(untitled) (Research, Society and Development, 2026)
Southern Africa bears the highest global burden of HIV, and the COVID-19 pandemic posed an unprecedented threat to antiretroviral therapy (ART) delivery systems. This study aimed to comparatively synthesize evidence on ART disruption, determinants of treatment abandonment, and epidemiological consequences across Southern Africa during the pandemic. A systematic review was conducted following PRISMA guidelines. Databases including PubMed, Scopus, Web of Science, and grey literature sources were searched for studies published between January 2020 and December 2025. Eligible studies reported ART adherence, retention, or service disruption in Southern African countries. Data were extracted and synthesized using a structured comparative framework. Evidence from Mozambique, South Africa, Malawi, and multi-country modelling studies revealed that ART delivery systems were relatively resilient, while diagnostic and support services were substantially disrupted. Key determinants of treatment interruption included mobility restrictions, transport barriers, fear of COVID-19 infection, and suspension of community-based services. Mathematical models predicted that a 6-month interruption in ART among 50% of patients could increase HIV-related mortality by 1.63-fold, corresponding to approximately 296,000 excess deaths in sub-Saharan Africa. Despite disruptions, several settings maintained viral suppression through adaptive strategies such as multi-month dispensing. The COVID-19 pandemic exposed critical structural vulnerabilities in HIV care systems, particularly in community service delivery and patient access. Ensuring uninterrupted ART supply and strengthening decentralized service models are essential to mitigate future health-system shocks.